THE ROLE OF COMPETITION IN THE TECHNO-ECONOMIC PARADIGM ON THE MARKET - Güler Aydin, Derya; Araz Takay, Bahar (Economic Annals, 2012)
Two different forms of competition theories can be distinguished: theories that emphasize the equilibrating forces created by competition, and those emphasizing the disequilibrating forces. This difference can be attributed, to the differences regarding the functioning of the market economy: the basic problem here is whether competition should be understood as a static state or a dynamic process. This study aims to analyse the dynamic competition theories by J. A. Schumpeter and neo-Schumpeterians which focus on the dynamic role played by competition through creating disequilibria, endogenous structural change and social transformation as a distinguishing characteristic of the market system. In the first section, after examining the static, neoclassical competition theory, Schumpeter’s theory, which is based on the notion of “creative destruction”, will be discussed. In the second section, the long term fluctuations based on the creative gales of the destruction concept will be examined in the framework of the techno-economic paradigm.